2016
DOI: 10.1007/s00508-016-1060-3
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of necrotizing fasciitis caused by Vibrio cholerae O8 in an immunocompetent patient

Abstract: We report a case of necrotizing fasciitis of the leg caused by Vibrio cholerae O8 in a 63-year-old immunocompetent man after he had been fishing in a lake on a Croatian island. The strain was cytotoxic, invasive and adhesive and contained a fragment of the gene for El Tor-like hemolysin (El Tor hlyA). After surgical and antibiotic treatment, the patient fully recovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Sixteen cases of necrotizing fasciitis caused by NOVC have been previously reported (Table 2) [9][10][11][12][13][14][15][16][17]. The majority of patients were exposed to seawater or had an injury.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen cases of necrotizing fasciitis caused by NOVC have been previously reported (Table 2) [9][10][11][12][13][14][15][16][17]. The majority of patients were exposed to seawater or had an injury.…”
Section: Discussionmentioning
confidence: 99%
“…NOVC bacteremia is strongly related to exposure to coastal or estuarine water or consumption of seafood, particularly oysters. 22,23 Many NOVC stains have been isolated in the coastal waters of countries such as Germany, India, South Korea, and France. [24][25][26][27] Our review found that 47.8% of patients (11/23) had a possible source of infection; 6 cases were attributed to consuming seafood and 4 to contaminated water.…”
Section: Mode Of Transmissionmentioning
confidence: 99%
“…29,30 Furthermore, several new virulence gene variants were reported in some environmental NOVC strains. 23 2018 A study suggested that NOVC can release outer membrane vesicles that induce miR-146a to induce colonization. 31 T3SS has also been demonstrated to facilitate colonization 32 and enhance the virulence of NOVC isolates.…”
Section: Pathogenesismentioning
confidence: 99%
“…Especially in Northern Europe (Baltic Sea), infections of swimmers have been predominantly caused by V. cholerae nonO1/nonO139 (Baker-Austin et al 2016b). Some serious infections of swimmers due to V. cholerae nonO1/nonO139 have also been reported from other European countries (Stypulkowska-Misiurewicz et al 2006;Huhulescu et al 2007;Sterk et al 2015;Dobrovic et al 2016;Engel et al 2016;Hirk et al 2016;Maraki et al 2016). The observed increase in infection frequency has been linked to global warming and the significantly increased water temperatures observed in many aquatic environments (Baker-Austin et al 2016b;Vezzulli et al 2016).…”
Section: Introductionmentioning
confidence: 99%